EVALUASI KEBIJAKAN PADAT KARYA TUNAI DI DESA PEKARUNGAN KECAMATAN SUKODONO KABUPATEN SIDOARJO - Muhammad Yusril Amar Setiawan; Suci Megawati (Publika, 2022)
Village cash labor intensive (PKTD) is a self-managed marginal community empowerment program that aims to create employment opportunities in order to reduce unemployment and poverty in villages, but in its application there are still villages that are hesitant, rarely even not implementing it. This study adopted a qualitative descriptive research, with the aim of evaluating the PKTD program in Pekarungan Village with 5 evaluation indicators according to Dale which include effectiveness, efficiency, relevance, impact, and sustainability. The data collection method is through in-depth interviews and documentation as well as for data analysis techniques, the authors adopt qualitative data analysis consisting of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Pekarungan Village PKTD had met the indicators of effectiveness and impact. Meanwhile, the indicators of efficiency, relevance, and sustainability have not been met adequately, because there are findings that the Pekarungan Village PKTD has not met the 50% wage rate requirement, its activities are still outside the home so that it is less relevant to the current pandemic conditions and there has been no sustainability action from the parties. village after the PKTD project is completed. The government should improve the content of the PKTD policy with the point of giving strict sanctions but also providing space for the village to adjust to local conditions so that the PKTD program is routinely implemented and will be able to reduce unemployment and poverty in the village optimally.